2020
DOI: 10.1177/2048872619886307
|View full text |Cite
|
Sign up to set email alerts
|

Utility of shock index in 24,636 patients presenting with acute coronary syndrome

Abstract: Background: Shock index is a bedside reflection of integrated response of the cardiovascular and nervous systems. We aimed to evaluate the utility of shock index (heart rate/systolic blood pressure) in patients presenting with acute coronary syndrome (ACS). Methods: We analyzed pooled data from seven Arabian Gulf registries; these ACS registries were carried out in seven countries (Qatar, Bahrain, Kuwait, UAE, Saudi Arabia, Oman and Yemen) between 2005 and 2017. A standard uniform coding strategy was used to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…However, the predictive accuracy of SI is not adequate. The AUC values for in-hospital and one-year mortality were 0.703 and 0.660, respectively ( 10 , 29 ). Renal dysfunction is believed to be a risk factor for patients with STEMI ( 1 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the predictive accuracy of SI is not adequate. The AUC values for in-hospital and one-year mortality were 0.703 and 0.660, respectively ( 10 , 29 ). Renal dysfunction is believed to be a risk factor for patients with STEMI ( 1 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“… 29 - 32 A study on 24 636 subjects suffered from ACS with optimal SI cut-off point of 0.80 showed patients who had higher values experienced 3.40 times (95% CI: 2.29-5.02, P < .001) increased chance of in-hospital death compared to those with lower SI ranges. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that the SI is a convenient and simple clinical tool that can permit rapid risk stratification of patients with AMI. 1,2 Moreover, several studies have demonstrated that, relative to the original SI, the age SI (age multiplied by the admission SI) is a stronger predictor of in-hospital cardiovascular events, 6-month mortality, and long-term mortality among patients with ST-segment elevation myocardial infarction (STEMI). 3,4 However, the pathophysiological mechanisms underlying the association between the age SI and adverse outcomes among STEMI patients are unclear.…”
Section: Introductionmentioning
confidence: 99%